Nano- and micro-mechanics of polymer blends and composites - Karger-Kocsis, J. (Jozsef); Fakirov, Stoyko (Munich ; Cincinnati : Hanser, 2009)
'The aim of this book is to give a state-of-art overview on aspects of micro- and nanomechanics of polymers, polymeric blends and composites'--Provided by publisher.
Includes bibliographical references and indexes
Keywords: Polymeric composites -- Mechanical properties; Micromechanics; Microstructure; Nanostructured materials